Consequence of Resistance to Change on AI Readiness: Mediating–Moderating Role of Task-oriented Leadership and High-Performance Work System in the Hospitality Sector - Cai Li; Sheikh Farhan Ashraf; Saba Amin; Muhammad Nabeel Safdar (SAGE Open, 2023)
In the modern era of the fourth industrial revolution, where collaborative systems are the real innovation, people are still not prepared for the results of the third revolution, namely, artificial intelligence readiness (AIR). Hence, people didn’t have enough time to adapt to the change. This paper aimed to explore the impact of resistance to change on artificial intelligence readiness and also explores the mediating role of task-oriented leadership, moderating role of high-performance work system. The study employs a quantitative research design and collects data of 450 working employees from hospitality sector of Pakistan. SmartPLS is used to analyze structural equation modeling (SEM) to through mixed-methods approach. The study findings are consistent with the proposed study hypotheses that resistance to change has positively impacts RI readiness and task-oriented leadership. Furthermore, the findings also elaborate the mediation of task-oriented leadership between latent constructs and moderating role of high-performance work system between resistance to change and task-oriented leadership. The study concluded that the hospitality sector should focus on developing task-oriented leadership and high-performance work systems to overcome resistance to change and increase its AI readiness.